High-Gain Quad Array of Nonuniform Helical Antennas - Jelena Lj. Dinkić; Dragan I. Olćan; Antonije R. Djordjević; Alenka G. Zajić (International Journal of Antennas and Propagation)
We present a design of a high-gain quad array of nonuniform helical antennas. The design is obtained by optimization of a 3-D numerical model of four nonuniform helical antennas placed above a ground plane, including a model of a feeding network, utilizing the method of moments with higher-order basis functions. The gain of one optimal nonuniform helical antenna can be about 2.5 dB higher than the gain of a uniform helical antenna of the same axial length. Creating a 2×2 array further increases the gain up to about 6 dB. The resulting quad array fits into a box whose dimensions are 2.5×3.3×3.3 wavelengths, and the gain in the main radiating direction is about 20.5 dBi in the frequency range from 0.9 GHz to 1.1 GHz. The design is verified by measurements of a prototype of the quad array.